The intersection of COVID‐19, school, and headaches: Problems and solutions. Issue 1 (31st December 2020) - Karvounides, Dina; Marzouk, Maya; Ross, Alexandra C.; VanderPluym, Juliana H.; Pettet, Christina; Ladak, Ali; Ziplow, Jason; Patterson Gentile, Carlyn; Turner, Scott; Anto, Marissa; Barmherzig, Rebecca; Chadehumbe, Madeline; et al.
Abstract: Objective: To equip clinicians with recommendations specific to concerns related to the novel coronavirus disease 2019 (COVID‐19), which impact the physical, emotional, and social health of youth with headache disorders. Background: COVID‐19 has affected societies on a global scale including children and youth with chronic headache disorders. Many concerns are predicted to arise in the 2020–2021 school year, whether classes are conducted in‐person or virtually. Methods: Clinical impressions were combined with a review of the literature, although limited due to the recent nature of this issue. Results: We describe recommendations to support caregivers and youth as they face changes expected with the return to school in the fall of 2020. Conclusion: Although there are significant concerns for caregivers and youth with migraine given the context of changes related to the pandemic, there are many recommendations that can help minimize exacerbations of the physical, emotional, and social health of youth with chronic migraine.